EFEKTIVITAS BELANJA DAERAH DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI PADA KABUPATEN/KOTA PROVINSI SUMATERA UTARA - MALAU, EVE; Widia Octari Diliana; Indah Mutiara; Hasmarini Ariestin Waruwu (Accounting Global Journal, 2026)
Economic growth between districts/cities in North Sumatra Province still shows significant variation. This study aims to analyze the effect of regional spending effectiveness on economic growth in districts/cities in North Sumatra Province during the 2020–2024 period. The study population includes all district and city governments in North Sumatra Province, with a sample size of 33 regions. The data used are secondary data obtained from publications of the Directorate General of Fiscal Balance and the Central Statistics Agency. The analysis technique used is descriptive statistics, panel data regression with the help of EViews software with the Chow test, Hausman test, and Lagrange Multiplier (LM) to determine the best model. The results show that regional spending effectiveness has a positive and significant effect on economic growth with a coefficient value of 0.0624 and a probability of 0.0002 (<0.05). The Adjusted R² value of 0.0841 indicates that regional spending effectiveness explains 8.41% of the variation in economic growth in the region, while the remainder is influenced by other factors outside the model. These findings sufficiently emphasize the importance of increasing regional spending effectiveness to encourage sustainable regional economic growth. Further research is recommended to add other fiscal variables and extend the observation period to obtain more comprehensive results. Keywords: Economic Growth, Regional Spending Effectiveness, Sustainability, Fiscal.